Д) (y-4) (3y-4)

Д) (y-4) (3y-4)

  • Д) 3у в квадраті-4у-12У + 16 = 3у в кв.-16У + 16
    е) 36а в квадраті-6а-30а + 5 = 36а в кв.-36а + 5
    ж) 6b в квадраті-4b + 9b-6 = 6b в кв. + 5b-6
    з) 7z в квадраті-21z-2z + 6 = 7z в кв.-23z + 6
  • Д) (у-4) (3у-4) = 3у (в квадраті) -4у -12у + 16 = 3у (в квадраті) -16у +16.
    е) (6а-5) (6а-1) = 36а (в квадраті) - 6а - 30а +5 = 36а (в квадраті) - 36а + 5.
    ж) (2в + 3) (3в-2) = 6в (в квадраті) -4В + 9в -6 = 6в (в квадраті) + 5в -6.
    з) (7z-2) (z-3) = 7z (в квадраті) - 21z- 2z + 6 = 7z (в квадраті) - 23z + 6.

Понравилась статья? Поделись с друзьями:
Добавить комментарий

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

+ 59 = 68